DAMPs Synergize with Cytokines or Fibronectin Fragment on Inducing Chondrolysis but Lose Effect When Acting Alone - Lei Ding; Joseph A. Buckwalter; James A. Martin (Mediators of Inflammation)
Objective and Design. To investigate whether endogenous damage-associated molecular patterns (DAMPs) or alarmins originated from mitochondria or nucleus stimulates inflammatory response in articular chondrocytes to cause chondrolysis which leads to cartilage degradation featured in posttraumatic osteoarthritis (PTOA). Materials. Primary cultures of bovine or human chondrocytes isolated from cartilage of weight-bearing joints. Treatment. Chondrocytes were subjected to mitochondrial DAMPs (MTDs) or HMGB1, a nuclear DAMP (NuD), with or without the presence of an N-terminal 29 kDa fibronectin fragment (Fn-f) or proinflammatory cytokines (IL-1β and TNF-α). Injured cartilage-conditioned culturing medium containing a mixture of DAMPs was employed as a control. After 24 hrs, the protein expression of cartilage degrading metalloproteinases and iNOS in culture medium or cell lysates was examined with Western blotting, respectively. Results. HMGB1 was synergized with IL-1β in upregulating expression of MMP-3, MMP-13, ADAMTS-5, ADAM-8, and iNOS. Moreover, a moderate synergistic effect was detected between HMGB1 and Fn-f or between MTDs and TNF-α on MMP-3 expression. However, when acting alone, MTDs or HMGB1 did not upregulate cartilage degrading enzymes or iNOS. Conclusion. MTDs or HMGB1 could only stimulate inflammatory response in chondrocytes with the presence of cytokines or Fn-f.